Evaluation of Vaccine Cold Chain Storage at Karangrejo Public Health Center in Tulungagung Regency in 2025 - Fatiya Nurul Izzah; Hajar Sugihantoro; Abdul Hakim; Novia Maulina; Roihatul Muti'ah (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Vaccine storage is an important aspect of vaccine cold chain management. If not done properly, it can cause vaccine damage, rendering the vaccine ineffective and unusable. This study aims to evaluate the suitability of vaccine storage at the Karangrejo Community Health Center in Tulungagung Regency based on the 2021 Guidelines for Vaccine Management in Health Care Facilities and Minister of Health Regulation No. 12 of 2017. This study used a descriptive qualitative method with an observational approach. Data were collected through direct observation using a checklist and interviews with personnel responsible for vaccine storage. The highest percentage of compliance was found in the vaccine storage condition indicator at 95% with 5% non-compliance, followed by the vaccine refrigerator condition at 89% with 11% non-compliance, storage facilities and infrastructure at 84% and 16% non-compliance, and vaccine refrigerator maintenance at 82% and 18% non-compliance. The conclusion of this study is that the cold chain management of vaccine storage at the Karangrejo Community Health Center in Tulungagung Regency achieved 87.5% compliance and 12.5% non-compliance with the 2021 Guidelines for Vaccine Management in Health Care Facilities and Minister of Health Regulation No. 12 of 2017.